POLA KOMUNIKASI KELUARGA DALAM PERSPEKTIF ISLAM - Samsinar S (fakultas Ushuluddin dan Dakwah IAIN Bone, 2020)
Abstract: Family of communication is the most important thing that must be maximized in maintaining family integrity. This communication can be done through communication between husband and wife, communication between parents and children, and communication between siblings. The pattern of communication can be done in a democratic manner through deliberation and consensus. Islamic highly upholds this principle, so that the various problems encountered must be resolved by deliberation and consensus, including in resolving conflicts that occur in the family. With these principles and patterns, the family will be harmonious and happy. Kata Kunci : communication, family, Islamic